UNDERSTANDING AND ATTITUDES OF RELIGIOUS MODERATION AT AL-AWWABIN ISLAMIC BOARDING SCHOOL IN DEPOK CITY - Ahmad Sujai; Muwahid Muhammadi; Abdurrahman; Zulfiqri (Almarhalah: Jurnal Pendidikan Islam, 2024)
ABSTRACK This research was conducted at Al-Awwabin Islamic Boarding School in Depok City with the aim of understanding the attitudes of religious moderation among the students (santri). The study is motivated by the fact that Depok ranks fifth as an intolerant city according to a study by Setara Institute in collaboration with the Presidential Unit for the Implementation of Pancasila Ideology (UKP-PIP). Al-Awwabin Islamic Boarding School was chosen as the location for community service with a focus on religious moderation education, with the hope of strengthening harmony and tolerance in the community of Depok City. Research at Al-Awwabin Islamic Boarding School involved 50 participants from among the students and local residents. The seminar held as part of the research activities was attended by Dr. Ahmad Sujai, MM., as Speaker I, Ust. Abdurrahman (Riri), M.Pd., as Speaker II, and Mr. A. Muwahid Muhammadi, S.HI, MM., as the Moderator. The research results indicate that the understanding of religious moderation at Al-Awwabin Islamic Boarding School is generally good. However, there is variation in the level of understanding among respondents. This data analysis provides a deeper understanding of the distribution and variation of attitudes towards religious moderation in the boarding school. Additionally, factors such as the educational background of the students, the social organization of the guardian parents, the teaching of religious moderation, and the leadership role (Kiai) also contribute to the understanding and attitudes of religious moderation at Al-Awwabin Islamic Boarding School.